Permission Marketing: An Analysis with Reference to Banking Promotional E-mails - Gupta, Nimit (Indian Journal of Marketing, 2015)
Permission marketing is a strategy which utilizes e-mail and mobile technology to send consumers information that they have agreed to receive. It seeks permission from the consumer to receive marketing messages. In short, customers volunteer to be marketed to. Permission marketing aims to build a customer group with a high-interest level by sending certain types of marketing information only to those who have specifically requested it. Banks require permission from customers before sending e-mails. Customers assess the behavior of banks and make a judgment about the integrity of a bank. The results of the present study revealed the factors which affected the permission given by customers to banks for sending promotional e-mails. The importance of the paper lies in the fact that it sheds light on the factors which affected the grant of permission based e-mails, the findings of which are presented in this paper. This research paper has implications for both academicians and the different practitioners who include bank marketers, especially practicing e-mail marketers in various capacities.